Pinnotheridae de Haan 1833 - González, José A. (Zenodo, 2018)
Pinnotheridae de Haan, 1833 Nepinnotheres pinnotheres (Linnaeus, 1758) —CNI Moreno et al. (1982, as Pinnotheres pinnotheres ); 2–25 m— Benthic, 6– 250 m. ATLM. Pinnotheres pisum (Linnaeus, 1767) —CNI Moro et al. (2014); 38 m—Benthic, 0– 150 m. EACT. Viridotheres marionae Manning, 1996 —CVI Manning (1996), type-locality; 91 m—Benthic. ECVI. Viridotheres viridis (Manning, 1993) —CVI Fransen (1991, as Pinnotheres spec.); 3–15 m—Benthic. ECVI. Taxa richness and characterising taxa. The number of marine families, genera and species/subspecies by higher taxa, as well as the percentage of the species from the total for both archipelagos is showed in Table 1. The percentage composition of the 10 higher taxa is very similar between both decapodal biotas, which are dominated by brachyuran and caridean species (Table 1). The current list of Canarian marine decapods comprises 374 species/ subspecies, grouped in 198 genera and 82 families; whereas the Cape Verdean marine decapods are currently represented by 343 species/subspecies, grouped in 200 genera and 79 families (Table 1). This comparative data gives an overwiew of the subject. However, it is evident that the Canary Islands have received much more sampling effort in the set of their different habitats, and this might be relevant to understand some differences found. It is widely accepted that the set of littoral and upper-bathyal taxa better characterize the marine fauna of one ecoregion and their zoogeographic affinities (e.g. González 2016; González et al. 2017c). With regard to taxa richness based on decapods living shallower than the insular upper slopes, some typically benthic families appear to be as relevant in terms of diversity (with relatively high number of genera) and specious (with at least 10 species/ subspecies in one archipelago) in both archipelagos. This is the case of the Hippolytidae, Palaemonidae and Pandalidae (Caridea), Paguridae (Anomura) and Leucosiidae, Epialtidae, Inachidae and Xanthidae (Brachyura) which are well represented in both biotas. However, the Galatheidae (8 vs. 4 species) and Paguridae (17 vs. 12) (Anomura) and Polybiidae (9 vs. 3) (Brachyura) appear to be more relevant for the Canarian decapod carcinofauna; whereas the Diogenidae (12 vs. 8) (Anomura) and Alpheidae (23 vs. 5) (Caridea) much better represent the Cape Verdean biota. Comparison of taxa composition. When compared both decapod catalogues, the Canary and Cape Verde Islands have divergent taxa composition taking into account the supra-species taxa (families and genera). The Canarian families Luciferidae (Dendrobranchiata), Stenopodidae (Stenopodidea), Bathypalaemonellidae, Glyphocrangonidae, Stylodactylidae (Caridea), Cancridae, Eriphiidae, Euryplacidae, Mathildellidae, Progeryonidae, Thiidae, and Cryptochiridae (Brachyura) do not currently occur in waters of the Cape Verde Islands. The Cape Verdean families Sicyoniidae (Dendrobranchiata), Disciadidae (Caridea), Hippidae (Anomura), Dynomenidae, Raninidae, Aethridae, Menippidae, Acidopsidae, Chasmocarcinidae, Mithracidae, and Ocypodidae (except for one specimen of Afruca tangeri probably introduced in the Canaries) (Brachyura) have not been found in waters of the Canaries. Dissimilarity in familiar taxa composition was 25%, i.e. 23 different families of the 93 decapod families occurring at both archipelagos combined. The Canarian genera Aristaeomorpha (Aristeidae), Bentheogennema (Benthesicymidae), Penaeopsis (Penaeidae), Solenocera (Solenoceridae), Allosergestes , Cornutosergestes , Deosergestes , Eusergestes and Sergestes (Sergestidae) within the Dendrobranchiata, Spongiocaris (Spongicolidae) within the Stenopodidea, Sabinea (Crangonidae), Nigmatullinus (Nematocarcinidae), Gnathophylleptum (Gnathophyllidae), Eupasiphae and Psathyrocaris (Pasiphaeidae) within the Caridea, Nephrops (Nephropidae) within the Astacidea, Pestarella (Callianassidae) within the Axiidea, Cardus (Polychelidae) within the Polychelida, Galacantha (Munidopsidae), Paguristes (Diogenidae), Paragiopagurus and Sympagurus (Parapaguridae) within the Anomura, Homologenus (Homolidae), Medorippe (Dorippidae), Rochinia (Epialtidae), Achaeus (Inachidae), Neomaja (Majidae), Polybius (Polybiidae), Nepinnotheres and Pinnotheres (Pinnotheridae) within the Brachyura do not currently occur in waters of the Cape Verde Islands. The Cape Verdean genera Aristeus (Aristeidae), Metapenaeopsis , Metapenaeus (Penaeidae) and Challengerosergia (Sergestidae) within the Dendrobranchiata, Microprosthema (Spongicolidae) within the Stenopodidea, Alpheopsis , Automate , Deioneus , Salmoneus (Alpheidae), Merhippolyte (Hippolytidae) and Parapontophilus (Crangonidae) within the Caridea, Callichirus , Corallianassa and Neocallichirus (Callianassidae) within the Axiidea, Ibacus (Scyllaridae) within the Achelata, Pachycheles , Petrolisthes (Porcellanidae), Ciliopagurus , Diogenes , Petrochirus , Pseudopagurus, Trizopagurus (Diogenidae), Acanthopagurus and Paguridium (Paguridae) within the Anomura, Sternodromia (Dromiidae), Sakaila (Aethridae), Phyllodorippe (Dorippidae), Epixanthus (Oziidae), Atlantolocia (Leucosiidae), Apiomithrax (Epialtidae), Daldorfia (Parthenopidae), Callinectes , Sanquerus (likely) (Portunidae), Eurypanopeus (Panopeidae), Paraxanthias , Xanthodius , one new undescribed genus of Xanthidae, Geograpsus (Grapsidae), Ocypode (Ocypodidae) and Viridotheres (Pinnotheridae) within the Brachyura have not been found in waters of the Canaries. Taking into account the genera of families absent from each other ecoregion, dissimilarity in generic taxa composition was 37%, i.e. 90 different genera (41 Canarian and 49 Cape Verdean) of the 245 decapod genera occurring at both archipelagos combined. At infra-generic level, 170 Canarian decapod species/subspecies do not currently occur in waters of the Cape Verde Islands, and 136 Cape Verdean decapod species/subspecies have not been found in waters of the Canaries. Dissimilarity in infra-generic taxa composition reached 60%, i.e. 306 different species of the 509 decapod species occurring at both archipelagos combined. When referred to littoral and upper-bathyal benthic forms, dissimilarity increased to 63%, i.e. 229 different species of the 365 decapod species present in both archipelagos combined. Comparison of species’ biogeographic patterns. A compared description of biogeographic patterns of decapod crustaceans from the Canary and Cape Verde Islands grouped by higher taxa is presented in Table 2. When compared littoral and upper-bathyal benthic pleocyemata species, the biogeographic composition at the Canaries resulted in favour of Atlanto-Mediterranean forms (ATLM), whereas this composition was quite different in the Cape Verdes with the tropical/subtropical component (TSEA) as dominant. Regarding the coastal benthic dendrobranchiate shrimps, the Canarian composition was dominated by pantropical species (PANT), whereas the Cape Verdean one was composed of two main biogeographic groups (TSEA and PANT) (Table 2). Rates of endemicity. In the Canaries three biogeographic groups accounted for their endemic components: ECAI, MAC, and ECNI. With regard to coastal benthic species, the ECAI group is represented by 9 species, and both the MAC and ECNI groups by 3 species each (Table 2). In the Cape Verdes other three biogeographic groups accounted for their endemics: ECAI, IWAF, and ECVI. With regard to coastal benthic species, the ECAI group is represented by 11 species, the IWAF by 1, and the ECVI by 22 (Table 2). Species probably tending to shift their distributions to higher latitudes. With regard to littoral and upperbathyal benthic species, the eastern Atlantic cold-temperate species (EACT), i.e. which generally have the Canary Islands as their southern limit of occurrence, are currently represented by 7 species (9.6%) within the Stenopodidea and Caridea combined, 13 species (23.7%) within the remaining Pleocyemata, and 21 species (16.8%) within the Brachyura (Table 2). ......continued on the next page Within the Cape Verdean coastal benthic species of warm affinity, the following numbers currently represent the decapod species not occurring (yet) in waters of the Canary Islands: 2 dendrobranchiates, 7 carideans, 3 axiideans, 2 gebiideans, 1 achelate, 12 anomurans, and 26 brachyurans within the TSEA group; 1 dendrobranchiate, 1 stenopodidean, 7 carideans, 1 achelate, 2 anomurans, and 3 brachyurans within the AAWA group; and 3 dendrobranchiates, 4 carideans, 1 achelate, 1 polychelidan, 1 anomuran, and 1 brachyuran within the PANT group; and surprisinly 1 ATLM anomuran species ( Pagurus mbizi ) (Table 3). Table 3 also includes 22 Cape Verdean warm-affinity decapod species recorded from the Canaries in the last 25 years. Lastly, Table 4 includes another six warm-affinity species recorded from the Canaries in the last 35 years, but not (yet) found in waters of the Cape Verde Islands. : Published as part of González, José A., 2018, Checklists of Crustacea Decapoda from the Canary and Cape Verde Islands, with an assessment of Macaronesian and Cape Verde biogeographic marine ecoregions, pp. 401-448 in Zootaxa 4413 (3) on pages 430-434, DOI: 10.11646/zootaxa.4413.3.1, http://zenodo.org/record/3769606 : {"references": ["Moreno, E., Bacallado, J. J. & Perez, J. M. (1982) Nueva contribucion al conocimiento de los crustaceos decapodos de las islas Canarias. In: Ros, J. & Niell, F. X. (Eds.), Actas del II Simposio Iberico de Estudio del Bentos Marino. Cuadernos de Biologia Marina del C. R. I. S., 3, Barcelona, pp. 213 - 219.", "Moro, L., Herrera, R., Ortea, J., Riera, R., Bacallado, J. J. & Martin, J. (2014) Aportaciones al conocimiento y distribucion de los decapodos y estomatopodos (Crustacea: Malacostraca) de las islas Canarias. Revista de la Academia Canaria de Ciencias, 26, 33 - 82.", "Manning, R. B. (1996) Viridotheres marionae, a new genus and species of pinnotherid crab from West Africa (Crustacea: Decapoda: Brachyura). Zoologische Mededelingen, 70, 271 - 273.", "Fransen, C. H. J. M. (1991) Preliminary report on Crustacea collected in the eastern part of the North Atlantic during the CANCAP and MAURITANIA Expeditions of the former Rijksmuseum van Natuurlijke Historie, Leiden. Nationaal Natuurhistorisch Museum, Leiden, vi + 200 pp.", "Gonzalez, J. A., Triay-Portella, R., Martins, A. & Lopes, E. (2017 c) Checklist of brachyuran crabs (Crustacea: Decapoda) from the Cape Verde Islands, with a biogeographic comparison with the Canary Islands (Eastern Atlantic). Cahiers de Biologie Marine, 58, 137 - 151. https: // doi. org / 10.21411 / CBM. A. 6 C 592127"]}